Validation of a cephalometric analysis designed for adolescents from Santiago de Cuba - Liuba González Espanglerá; Ayvanka León Quintela; Manuela Ricardo Reyes; Yumeidis Ramírez Quevedo; Maira Raquel Martínez Ramos (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: The variations of the different cephalometric analyses available have shown that many of their standards do not fit all patients, which could be due to the fact that they emerged in populations and contexts with different characteristics. Objective: To validate a cephalometric analysis designed for adolescents from Santiago de Cuba. Methods: A development investigation was carried out at Mártires del Moncada Provincial Stomatological Clinic in Santiago from Cuba from January, 2021 to February, 2023. Two random samples were studied, one of specialists for the selection of the variables to include in the design of the cephalometric analysis and another of experts for its validation. The validation of aspect, content and criterion was carried out implementing the Moriyama criteria. Results: The cephalometric analysis CefaloSan had 32 measures grouped in six areas that allowed to make a dental, skeletical, dentoskeletical, detemining, structural internal and of the soft tissues analysis. In the validation a global qualification of agreement was obtained among all the experts regarding the five criteria, evaluated with the maximum punctuation. They considered that CefaloSan is comprehensible, because it presents defined components and a justifiable topic, being derived from data that can be obtained and it is also sensitive to variations. The level of acceptance of the instrument exceeded 80 %, result that was statistically significant. Conclusions: The cephalometric analysis proposed constitutes a tool that will allow to achieve a more complete diagnosis of the patient, contextualizing it to the typical characteristics of Cubans and the diagnostic necessities.